2006
DOI: 10.1038/sj.bjc.6603073
|View full text |Cite
|
Sign up to set email alerts
|

Detection of occult carcinomatous diffusion in lymph nodes from head and neck squamous cell carcinoma using real-time RT–PCR detection of cytokeratin 19 mRNA

Abstract: The aim of the present study was to evaluate the occult lymph node carcinomatous diffusion in head and neck squamous cell carcinoma (HNSCC). A total of 1328 lymph nodes from 31 patients treated between 2004 and 2005 were prospectively evaluated by routine haematoxylin -eosin -safran (HES) staining, immunohistochemistry (IHC) and real-time Taqman reverse -transcriptase polymerase chain reaction (real-time RT -PCR) assay. Amplification of cytokeratin 19 (CK19) mRNA transcripts using real-time RT -PCR was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…The CK19‐positive rate in cancerous tissue of patients with oral squamous cell carcinoma was 91% detected using immunohistochemistry . It is considered to be a highly sensitive and useful marker for detecting lymph node metastasis in various types of cancer, including head and neck squamous cell carcinoma …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CK19‐positive rate in cancerous tissue of patients with oral squamous cell carcinoma was 91% detected using immunohistochemistry . It is considered to be a highly sensitive and useful marker for detecting lymph node metastasis in various types of cancer, including head and neck squamous cell carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…26 It is considered to be a highly sensitive and useful marker for detecting lymph node metastasis in various types of cancer, including head and neck squamous cell carcinoma. 27,28 This protein is expressed in most, but not all, breast cancer cases. Although the 1-step nucleic acid amplification assay has proven useful in breast cancer, this prevalent expression of CK19 suggests there is a risk of false negative results by the 1-step nucleic acid amplification assay when testing CK19-negative patients who have breast cancer 10 and, similarly, those with head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Micrometastases represent tumor deposits measuring less than 2 mm in diameter. As histopathological analysis of neck dissection specimens is usually performed on several 3-4-μm sections from each lymph node, micrometastases can be easily missed on routine light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This variability in clinical behavior has led to numerous studies on the relationships between the clinical, pathological, and, more recently, the molecular factors associated with tumor aggressiveness. Because metastatic lymph nodes are a major prognostic factor in oral and oropharyngeal SCCs, detection of occult cancer cells undetected by routine histopathology may identify N0 patients at high risk of recurrence, as has already been shown in other solid tumors …”
Section: Introductionmentioning
confidence: 91%
“…Because metastatic lymph nodes are a major prognostic factor in oral and oropharyngeal SCCs, detection of occult cancer cells undetected by routine histopathology may identify N0 patients at high risk of recurrence, as has already been shown in other solid tumors. [2][3][4][5] Routine histopathological examination easily overlooks micrometastatic tumor deposits within neck nodes of patients with head and neck SCC, consequently resulting in underestimation of the actual occult metastasis rate. 6 It has been reported that micrometastasis occurs in 3% to 7% of nodes and 9% to 22% of patients with clinically N0 necks.…”
Section: Introductionmentioning
confidence: 99%